Income inequality in the face of climate change: an empirical investigation on unequal nations, vulnerable regions and India - Swapnanil SenGupta; Aakansha Atal (SN Business & Economics, 2024)
Climate change is the paramount challenge of our era. While considerable attention has been given to its impact on financial stability and economic productivity, there is limited focus on its effects on income inequality. We introduce a unique criterion for sample selection. We aim to provide an empirical analysis of how climate change impacts income inequality in 43 most climate-vulnerable countries, 39 most unequal countries in terms of income distribution, and India separately (1971–2021). We select the most vulnerable countries to investigate the magnitude of income inequality caused by climate change. Given that climate hazards enhance inequality in countries with prevailing socioeconomic inequalities, we choose unequal countries to investigate whether climate change is a significant determinant of their existing condition. We also analyse the relationship for India because India is one of the most climate-vulnerable and unequal countries. We use three climate change indices—vulnerability to climate change, annual surface temperature change, and frequency of climate-related disasters—to check the effects of particular aspects of climate change. We deploy a standard panel regression analysis followed by a series of robustness checks and an autoregressive distributed lag (ARDL) bounds test approach to analyse the link for India. We find that climate change has adverse impacts in both groups and in India, both in the long and short term. Our findings suggest that policymakers in developing countries may need to equally place importance on developmental and climate change abatement goals as well as expedite their environmental targets.
Keywords: D31; O10; O15; Q54; 330; Climate change; Income inequality; Panel data; India; Fixed effects regressions; ARDL Bounds Test